Review of Herbal Traditional Chinese Medicine for the Treatment of Diabetic Nephropathy - Guang-dong Sun; Chao-yuan Li; Wen-peng Cui; Qiao-yan Guo; Chang-qing Dong; Hong-bin Zou; Shu-jun Liu; Wen-peng Dong; Li-ning Miao (Journal of Diabetes Research)
Diabetic nephropathy (DN) is the most serious chronic complications of diabetes; 20–40% of diabetic patients develop into end stage renal disease (ESRD). However, exact pathogenesis of DN is not fully clear and we have great difficulties in curing DN; poor treatment of DN led to high chances of mortality worldwide. A lot of western medicines such as ACEI and ARB have been demonstrated to protect renal function of DN but are not enough to delay or retard the progression of DN; therefore, exploring exact and feasible drug is current research hotspot in medicine. Traditional Chinese medicine (TCM) has been widely used to treat and control diabetes and its complications such as DN in a lot of scientific researches, which will give insights into the mechanism of DN, but they are not enough to reveal all the details. In this paper, we summarize the applications of herbal TCM preparations, single herbal TCM, and/or monomers from herbal TCM in the treatment of DN in the recent 10 years, depicting the renal protective effects and the corresponding mechanism, through which we shed light on the renal protective roles of TCM in DN with a particular focus on the molecular basis of the effect and provide a beneficial supplement to the drug therapy for DN.